Application of Symmetric Key Algorithm in Data Security Design of Smart Grid - Zhang, Yifan; Yu, Chaoyu; Wang, Yuqiang; Han, Junfei; Zhong, Ming; An, Haijun; Yuan, Ningping (2023 International Conference on Mechatronics, IoT and Industrial Informatics (ICMIII), 2023)
There are a large number of distributed transaction management in the smart grid. If the traditional centralized control method is adopted, it will cause problems such as low security level, privacy leakage and high maintenance cost. Protecting the privacy and security of data is the most important link in network transmission. The input of data parties will not interfere with each other, which protects the privacy of users. The research purpose of this paper is the application of symmetric key algorithm in smart grid data security design. In the experiment, according to the symmetric key security evaluation index, using the run-length test and frequency test methods, the data security design of the symmetric key algorithm in the smart grid is analyzed, thereby proving the security of the symmetric key algorithm.